Conference Review: The Interpretation of Nizami’s Cultural Heritage in the Modern Period (ENTHYMEMA, 2018)
Review of the conference "The Interpretation of Nizami’s Cultural Heritage in the Modern Period" organized by the Nizami Ganjavi International Centre and Azerbaijan Comparative Literature Association. Baku, Azerbaijan, 13-14th March 2018.
Keywords: Nizami; literary-cultural heritage; comparative analysis; regional motifs; Azerbaijani ashug